(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The Bellerophon (Late Permian) and Werfen (Lower Triassic) Formations were investigated on the basis of conodonts. Fifteen sections were sampled from Carnic Alps and Dolomites area in the Southern Alps. Ten were productive. The Bellerophon Formation yielded a few specimens of Hindeodus typicalis, Ellisonia agordina and Ellisonia sp. In the Werfen Formation were collected Hindeodus typicalis, Ellisonia agordina, E. triassica, Hadrodontina anceps, Xaniognathus gradatus, Isarcicella isarcica, Pachycladina obliqua, Ellisonia delicatula, Neospathodus triangularis. In describing the conodont fauna, multielement taxonomy is applied. Ellisonia agordina is a new species found at the top of the Bellerophon Formation and from the Tesero to the Siusi Members of the Werfen Formation, i, e. at the Permian — Triassic boundary and in the Lower Triassic. The apparatus of this new species is described. In the Southern Alps the range of Hindeodus typicalis, previously known in the Werfen Formation, extends down into the uppermost Bellerophon Formation. All species confirm the ranges found elsewhere in the world. On the basis of only the conodont fauna, it is not possible as yet to recognize the position of the Permian — Triassic boundary more precisely in the Bellerophon/Werfen Formations in the Southern Alps. It is obvious, however, that the recovery of Isarcicella isarcica allows the certain identification of the Triassic.